The effect of celecoxib in traumatic heterotopic ossification around temporomandibular joint in mice. Issue 4 (April 2020) - Ouyang, N.; Zhao, Y.; Chen, Q.; Chen, L.; Fang, B.; Dai, J.; Shen, G.
Summary: Objective: In this study, the role of inflammation in traumatic heterotopic ossification around temporomandibular joint (THO-TMJ), as well as the preventive and treatment effect of celecoxib in THO-TMJ both in vivo and in vitro were explored. Design: A surgically-induced THO-TMJ mouse model and a co-culture model of ATDC-5 or MC3T3-E1 and RAW-264.7 cells were used in this study for in vivo and in vitro research. Results: A series of inflammatory factors, such as CD3, CD68, CD20, IL-10, IL-6 and TNF-α, were activated 48 h after trauma in a THO-TMJ model. Local trauma initiated systemic inflammatory responses as well as T cell- and macrophage-mediated local inflammatory responses around TMJ. In addition, expression of COX-2 was significantly elevated. The findings also showed that local injection of celecoxib could effectively alleviate the inflammatory response around TMJ at the early stage of trauma and inhibit the formation of THO-TMJ in vivo . Meanwhile, celecoxib could inhibit chondrogenic differentiation of ATDC-5 and osteogenic differentiation of MC3T3-E1 under inflammatory condition in vitro . Furthermore, celecoxib could inhibit the expression of Bmpr1b in the injured condylar cartilage at the initiation stage of THO-TMJ, which implied that Bmpr1b expressed by the residual condylar cartilage might be related to the pathogenesis of THO-TMJ. Conclusions: Inflammation played a crucial role in the pathogenesis of THO-TMJ, and anti-inflammation might be a possible choice to inhibit THO-TMJ, which provided scientific clues for the mechanisms, pharmacotherapy and molecular intervention of THO-TMJ.